Effects of neonatal handling on behavior and stress-response in rats selected for reaction towards humans - Yu. E. Herbeck; O. A. Amelkina; M. Yu. Konoshenko; S. G. Shikhevich; R. G. Gulevich; R. V. Kozhemyakina; I. Z. Plyusnina; I. N. Oskina (Вавиловский журнал генетики и селекции, 2016)
It is known that neonatal handling may cause longterm changes in neurobiological and behavioral phenotypes. Neonatal handling of rats selected for enhanced aggressiveness towards humans (“aggressive” rats of generation 44) significantly mitigated aggression and stress responsiveness. However, levels of corticosterone in stress in intact aggressive rats of later generations (70s) were lower than in generation 44, which differed little from the corresponding value in “tame” rats, selected in the opposite direction, for the absence of aggressiveness towards humans. The study was conducted with Norway rat populations of the 75th generation of selection for aggressive and tame behavior, respectively. The goal was to find out whether the decrease in stress response in aggressive rats at the current stage of selection was accompanied by a decrease in the influence of handling on aggressiveness. It was found that neonatal handling of aggressive animals caused a significant decrease in aggressiveness, although considerably smaller than in generation 44. In both aggressive and tame rats, the blood corticosterone level at stress was getting back to the basal level for a longer time than in the corresponding control groups. Neonatal handling decreased the amount of mRNA for the glucocorticoid receptor (GR) in the hippocampus of aggressive rats but did not affect significantly the amount of mRNA for the corticotropin-releasing hormone (CRH) in the hypothalamus. However, higher contents of CRH mRNA were recorded in aggressive rats than in tame ones in the control groups. However, no differences in glucocorticoid receptor mRNA  were found between the strains in contrast to earlier generations. It was shown that neonatal handling was beneficial for maternal behavior in tame rats. Thus, the results obtained in the 75th generation of selection indicate that the effect of handling on aggressiveness weakens with decreasing stress responsiveness in aggressive rats. This is likely to be related to the changing amount of GR in the hippocampus and stronger glucocorticoidmediated feedback at the current stage of selection. The minor prolongation of the stress response appears to be related to the stressing component of neonatal handling rather than to changes in maternal care.